PENGEMBANGAN INKUBATOR BISNIS BERBASIS PESANTREN UNTUK MENDUKUNG KINERJA BISNIS TENANT UMKM - Persada, Alif Ringga; Afridah, Mumtaz; Wijayanti, Rani Ika; Kushardiyanti, Dessy; Atikoh, Nur; Susilowati, Anggi Yus; Aisyiyah, Muhsiyana Nurul; Hasim, Wakhit (Holistik: Journal for Islamic Social Sciences, 2024)
Community Skills Training Centers (BLKK) were initiated and established by the Indonesian Ministry of Manpower and Cooperatives by providing initial facilities in terms of infrastructure and programs funded directly by the government. Several BLKKs in Region II of West Java were developed in Islamic boarding schools (pesantren). In 2024, BLKK was encouraged to develop and expand its businesses by establishing business incubators. In doing so, this effort was mentored and facilitated by UIN Siber Syekh Nurjati Cirebon throughout 2024. This paper examines the achievements of mentoring community-based BLKKs in Region II of West Java in developing business incubators to expand their businesses. The research for this paper was conducted qualitatively, with informants consisting of BLKK program implementers and mentors. The analysis was conducted using an evaluation scheme based on the business incubator roadmap developed by the Indonesian Ministry of Manpower. The results of this study show that, firstly, there is a need for the development of UMKM businesses run by BLKKs towards business incubators to expand their businesses, although they face challenges such as a lack of financial support, a lack of awareness among potential tenants, and a lack of government support. Secondly, business incubators play an important role in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) and tenants in Indonesia. Case studies at Community Skills Training Centers show that business incubators not only provide skills training but also help MSMEs and tenants access technology, improve human resource quality, and gain broader market access. BLKK incubators serve as intermediaries between MSMEs and the industrial world, enabling the creation of collaborations relevant to local market needs. Business incubation also helps to overcome the main challenges faced by MSMEs, such as limited capital, limited access to technology, and challenges in facing digital transformation.